2020
DOI: 10.1242/dev.190181
|View full text |Cite
|
Sign up to set email alerts
|

TCF7L2 regulates postmitotic differentiation programs and excitability patterns in the thalamus

Abstract: Neuronal phenotypes are controlled by terminal selector transcription factors in invertebrates, but only a few examples of such regulators have been provided in vertebrates. We hypothesised that TCF7L2 regulates different stages of postmitotic differentiation in the thalamus, and functions as a thalamic terminal selector. To investigate this hypothesis, we used complete and conditional knockouts of Tcf7l2 in mice. The connectivity and clustering of neurons were disrupted in the thalamo-habenular region in Tcf7… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 102 publications
0
22
0
Order By: Relevance
“…We also found that astrocytes play a critical and non-neuron autonomous role in regulating neuronal function. This highlights the importance of considering cell-type specific effects when evaluating the numerous roles of Wnt signalling in synapse maturation, stability and strength 40 , including recent studies from our group showing that TCF7L2 directly regulates the expression of genes involved in neurotransmission 16 . The mechanism by which excitability of cortical neurons is decreased in mice with TCF7L2-deficient astrocytes requires further investigation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We also found that astrocytes play a critical and non-neuron autonomous role in regulating neuronal function. This highlights the importance of considering cell-type specific effects when evaluating the numerous roles of Wnt signalling in synapse maturation, stability and strength 40 , including recent studies from our group showing that TCF7L2 directly regulates the expression of genes involved in neurotransmission 16 . The mechanism by which excitability of cortical neurons is decreased in mice with TCF7L2-deficient astrocytes requires further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…In canonical Wnt signaling, β-catenin translocates to the nucleus and acts as a cofactor for the LEF1/TCF transcription factors to activates target gene expression 13 . TCF7L2 is a Wnt effector with a particularly prominent role in brain development, including promoting proliferation of radial glia 14 , driving oligodendrocyte maturation 15 and regulation of terminal selection of thalamic neurons 16 TCF7L2 is expressed in both human and murine astrocyte lineage cells 1718 and may play a role in astrocyte specification 19 . However, whether it plays a role in astrocyte maturation is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the telencephalon was enriched in EMX1/2, which regulate proliferation and specification of radial glial cells (Bishop et al, 2003). The diencephalon was enriched in transcription factors involved in thalamus specification (e.g., TCF7L2, BARHL2 and DBX1) (Lipiec et al, 2020;Vue et al, 2007). EN1/2 were enriched in the anterior and posterior midbrain and are known to regulate dopaminergic neuron specification (Alves dos Santos and Smidt, 2011).…”
Section: Spatiotemporal Dynamics Of Gene Regulation In Mouse Organogenesismentioning
confidence: 99%
“…Therefore, the default fate of a dHb precursor cell in a Wnt signaling devoid environment is to become a dHbl neuron. Recent evidence from mouse experiments suggests that this function of Wnt/beta-catenin signaling to influence habenular neuron diversity in postmitotic precursor cells is evolutionarily well conserved [ 26 ]. A major difference between these two animal models is that in zebrafish, Wnt/beta-catenin is suppressed in the environment of left-sided nascent habenular neurons in the presence of the parapineal, which results in clear differences in the size of neuronal populations between the left and right side.…”
Section: The Zebrafish Habenular Network and Tools For Manipulatiomentioning
confidence: 99%
“…In particular, studies using the zebrafish animal model system have revealed that the risk genes for schizophrenia and autism, tcf7l2 and wif1 [ 20 , 21 , 22 , 23 ], are crucial regulators of habenular neurogenesis and axonal targeting [ 24 , 25 ]. Some of these works have now begun to be repeated in the mouse model [ 26 ] highlighting the evolutionary conservation of important aspects of the mechanisms underlying habenular neural circuit formation. Even though causative genes of mental disorders normally differ, and syndromes are defined by distinct behavioral abnormalities, patients also display striking similarities such as anxiety, disturbed social behavior, reduced motion, and mood dysfunction [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%